The Urgency of the 5C Principle in Minimizing Financing Risk at Bank Syariah Indonesia KC Diponegoro - Rizki Andriyani; Muhammad Kurniawan; Gustika Nurmalia (Majapahit Journal of Islamic Finance and Management, 2025)
The purpose of this study was to analyze the urgency of the application of the 5C principles in minimizing the risk of financing at Bank Syariah Indonesia KC Diponegoro. This research includes a type of Field Research (field research) which is essentially a method to find specifically and realistically about what is happening in society. As for the informants in this study amounted to 5 people who consist of employees of bank BSI AFO Division (Area Financing Operation) and customers of Bank Syariah Indonesia (BSI) KC Bandar Lampung. Overall, the application of the 5c principles includes character assessment through interviews and track records, Capacity through business observation and cash flow analysis, Capital from the customer's initial capital, Collateral as additional liquid and legal security, and Condition through environmental economic analysis is a comprehensive approach that is essential in mitigating financing risks in Islamic banking. This study implies that the optimal application of the 5C principles (Character, Capacity, Capital, Collateral, and Condition ) can significantly minimize the risk of financing at Bank Syariah Indonesia KC Diponegoro, resulting in a positive impact on the financial health and sustainability of the bank's operations. This study offers an original perspective by specifically analyzing the urgency of implementing the 5C principles (Character, Capacity, Capital, Collateral, Condition) in minimizing financing risks at Bank Syariah Indonesia KC Diponegoro, filling the void of in-depth empirical studies on Sharia entities in the region.